Comparing GOSAT observations of localized CO2 enhancements by large emitters with inventory‐based estimates. Issue 7 (2nd April 2016) - Janardanan, Rajesh; Maksyutov, Shamil; Oda, Tomohiro; Saito, Makoto; Kaiser, Johannes W.; Ganshin, Alexander; Stohl, Andreas; Matsunaga, Tsuneo; Yoshida, Yukio; Yokota, Tatsuya
Abstract: We employed an atmospheric transport model to attribute column‐averaged CO2 mixing ratios ( X CO2 ) observed by Greenhouse gases Observing SATellite (GOSAT) to emissions due to large sources such as megacities and power plants. X CO2 enhancements estimated from observations were compared to model simulations implemented at the spatial resolution of the satellite observation footprint (0.1° × 0.1°). We found that the simulated X CO2 enhancements agree with the observed over several continental regions across the globe, for example, for North America with an observation to simulation ratio of 1.05 ± 0.38 ( p  < 0.1), but with a larger ratio over East Asia (1.22 ± 0.32; p  < 0.05). The obtained observation‐model discrepancy (22%) for East Asia is comparable to the uncertainties in Chinese emission inventories (~15%) suggested by recent reports. Our results suggest that by increasing the number of observations around emission sources, satellite instruments like GOSAT can provide a tool for detecting biases in reported emission inventories. Key Points: GOSAT estimated CO2 abundance due to large emitters compared to inventory‐based estimate Observed and inventory‐based CO2 abundance agree well over global and subcontinental scales Observation‐model discrepancy (22%) over East Asia is close to uncertainty in emission inventory